IMU 601: Fiqh Muqaran. Case Study: Paying Zakat for Asnaf and Non-Asnaf / Ainul Fatinah Dayini Mohd Sabri … [et al.] - Mohd Sabri, Ainul Fatinah Dayini; Norlizal, Norain Husna; Roslan, Ruhil Farhanim; Sabri, Nur Huda Syazana; Abdul Moin, Nur Asyiqin (2023)
Zakat can be defined as the blessing, growing, clean and good. In other words, zakat has the meaning of cleansing oneself from envy and revenge towards others. Fuqaha Mazhab Syafii defines zakat as a rate determined from several types of property that must be issued by certain groups with certain conditions. As you know, zakat can improve a person's standard of living. However, despite the increase in the amount of zakat collection and distribution, the number of the poor and needy has also increased over time. This is because zakat should be given to certain groups as prescribed by Allah SWT in Surah Al-Tawbah; 103; With this, zakat cannot be given to those who do not have the right to receive it, but it is allowed for some specific circumstances other than the 8 groups that have been mentioned. Besides that, based on Muhammad Dahan's study (1988), bureaucratic problems in zakat institutions are also one of the causes of zakat distribution problems that cannot be distributed properly. This will cause prospective zakat players to be more inclined to continue paying zakat to their closest relatives who do not belong to the asnaf group without going through the zakat center due to the trust not being properly maintained. If this problem is not curbed, not only will there be a problem with zakat collection, but the poverty rate will continue to increase and cause an economic recession. So this problem must be overcome to ensure that zakat payers can use official channels and that zakat can be channeled to the right people.